Poverty and politics in Tocqueville’s Memoir on Pauperism - HENDERSON, Christine Rodman (Institutional Knowledge at Singapore Management University, 2014)
Alexis de Tocqueville (1805-1859) is best remembered in the United States for Democracy in America, his penetrating study of life in the early nineteenth-century. Tocqueville was, of course, an analyst of his own France, and his The Old Regime and the Revolution remains a classic analysis of pre-Revolutionary and Revolutionary France. Less well-known, however, is that Tocqueville was also keenly interested in England, traveling to England several times and following with great interest the political and social developments there during his lifetime. One outgrowth of his interest in England’s politics was his Memoir on Pauperism, a short piece written following an 1833 visit to England and delivered to the Royal Academy in Cherbourg in 1835. This memoir, which was not included in the early editions of Tocqueville’s collected works and which was not even translated into English until 1968, captures England at a very specific moment, as her Elizabethan-era poor laws were undergoing major revision, via the Poor Law Amendment Act of 1834. Tocqueville ’s analysis continues to speaks to us today, offering fresh insights into the moral hazards associated with welfare programs, and challenging us—as advocates of a free and beneficent society—to seek better alternatives to these problems in our own times. Tocqueville develops his thoughts about state-based aid programs by presenting a series of three paradoxes which give organizational shape to the Memoir.